An Edge Crack Torsion Method for Mode III Delamination Fracture Testing - Shaw Ming Lee
A new fracture toughness test, the edge crack torsion method, has been developed for characterizing the mode III delamination behavior of composites. The test is based on a laminate specimen subjected to torsion to propagate an edge delamination crack in its midplane. The crack growth mode of the specimen has been deduced to be mode III from fracture mechanics principles. The torsional behavior and the corresponding fracture parameter Gmc have been analyzed on the basis of plate torsion and laminate theory. Edge crack torsion tests were performed to measure G,Hc of several carbon fiber/epoxy composite systems. Laminate layups were optimized to yield linear elastic fracture behavior of the specimens. The specimens were also sufficiently compliant to allow Gmc to be readily obtained by using the compliance calibration method. The deformation characteristics of the specimens were found to follow the laminate torsion description. SEM observations showed fracture surface morphology varying with resin microstructures and, for the case of an untoughened matrix, were consistent with what was reported in the literature for other proposed mode III fracture tests.
Keywords: FRACTURE; LAMINATES; COMPOSITE MATERIALS; DELAMINATION; MODE III TESTING; FRACTURE TOUGHNESS; FRACTURE MECHANICS; TORSIONAL DEFORMATION